Targeting a Reticulocyte Binding Protein and Duffy Binding Protein to Inhibit Reticulocyte Invasion by Plasmodium vivax - Gupta, Sonal (Sci Rep, 2018)
Plasmodium vivax merozoite invasion is restricted to Duffy positive reticulocytes. Merozoite interaction with the Duffy antigen is mediated by the P. vivax Duffy binding protein (PvDBP). The receptor-binding domain of PvDBP maps to an N-terminal cysteine-rich region referred to as region II (PvDBPII). In addition, a family of P. vivax reticulocyte binding proteins (PvRBPs) mediates interactions with reticulocyte receptors. The receptor binding domain of P. vivax reticulocyte binding protein 1a (PvRBP1a) maps to a 30 kD region (PvRBP1a(30)). Antibodies raised against recombinant PvRBP1a(30) and PvDBPII recognize the native P. vivax antigens and inhibit their binding to host receptors. Rabbit IgG purified from sera raised against PvRBP1a(30) and PvDBPII were tested individually and in combination for inhibition of reticulocyte invasion by P. vivax field isolates. While anti-PvDBPII rabbit IgG inhibits invasion, anti-PvRBP1a(30) rabbit IgG does not show significant invasion inhibitory activity. Combining antibodies against PvDBPII and PvRBP1a(30) also does not increase invasion inhibitory activity. These studies suggest that although PvRBP1a mediates reticulocyte invasion by P. vivax merozoites, it may not be useful to include PvRBP1a(30) in a blood stage vaccine for P. vivax malaria. In contrast, these studies validate PvDBPII as a promising blood stage vaccine candidate for P. vivax malaria.